The Security of the Russian Federation and the National Legal System - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2022)
In the article, considering one of the most controversial concepts in the theory of law, as a national legal system, it is substantiated that such negative legal phenomena as contradictions in law, its gaps, legal nihilism, etc., should not be included as structural elements of legal system, because the latter is the result of the activity of the state, created to solve its goals and objectives, acting as one of the most important aspects of the sovereignty of the state, which, in turn, is the main subjects that ensure national security.